Effects of godawariphosgold and single super phosphate on groundnut (Arachis hypogaea) productivity, phosphorus uptake, phosphorus use efficiency and economics - YADAV, GULAB SINGH; BABU, SUBHASH; MEENA, RAM SWAROOP; DEBNATH, CHANDAN; SAHA, POULAMI; DEBBARMA, CHIRANJIT; DATTA, M (The Indian Journal of Agricultural Sciences, 2017)
The field experiment was conducted at Agronomy experimental plot of ICAR Research Complex for North East Region, Tripura Centre, Lembucherra, Tripura (W), India, to study the effects of different sources of phosphorus (P) at varying rates of application on yield, P uptake, economics and P use efficiency of groundnut. The experiments were laid out in a split-plot design with 3 replications. The treatments were consisted of 2 phosphate fertilizers [Godawariphosgold (GPG) and single super phosphate (SSP)] in main plots and 4 rates of application (control, 9, 18 and 27 kg P/ha) in sub-plots. Phosphorus applied through GPG produced significantly higher pod yield (1.86 to 1.93 tonnes/ha) and haulm yield (3.16 to 3.29 tonnes/ha) as compared to SSP. The application of P through GPG increased the pod and haulm yield 7.5 to 16.7% and 7.3 to 15.2%, respectively over SSP. Application of 27 kg P/ha through GPG produced highest pod and haulm yield. The groundnut plot treated with GPG recorded significantly more Puptake (15.6 to 15.9 kg/ha) as compared to SSP treated plots (13.3 to 13.9 kg/ha). P uptake was highest, when 27 kg P/ha was applied through GPG.Application of P through GPG significantly increased the agronomic efficiency (15.4 to 24.4 kg grain yield increase/kg P applied) and apparent recovery (15.4 to 25.4%) compared to SSP. The highest net return (Rupees 71744/ha) was recorded with application of 27 kg P/ha through GPG, and highest B: C ratio (2.59) was noticed in groundnut plots, where 27 kg P/ha was applied through SSP. Therefore, we recommended that application of GPG at rate of 27 kg P/ha for increased productivity, P uptakes, P use efficiency and net returns in groundnut crop.